Performance Analysis of a Unidirectional Double E-Shaped Microstrip Antenna in the ISM Band - Natalia; Kamelia Quzwain; Levy Nur Olivia; Putri Rahmawati (Postgraduate, University of Mataram, 2025)
This research explores the design and simulation of a unidirectional double E-shaped microstrip antenna (MSA) operating at 5.8 GHz. The antenna was designed using CST Studio Suite, with Rogers RT 5880 as the substrate material due to its favorable dielectric properties. The design process involved adjusting the patch geometry by introducing slots to enhance bandwidth and gain. Simulation results show a return loss of −38.05 dB and a VSWR of 1.025, both indicating excellent impedance matching. Additionally, the antenna exhibits a directional radiation pattern with a peak gain of 7.63 dBi. These findings highlight the antenna's potential for compact and high-performance wireless communication systems in the ISM frequency band.